2020
DOI: 10.3390/rs12071174
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution and Risk Assessment of Heat Waves Based on Apparent Temperature in the One Belt and One Road Region

Abstract: Heat waves seriously affect the productivity and daily life of human beings. Therefore, they bring great risks and uncertainties for the further development of countries in the One Belt and One Road (OBOR) region. In this study, we used daily meteorological monitoring data to calculate the daily apparent temperature and annual heat wave dataset for 1989–2018 in the OBOR region. Then, we studied their spatiotemporal distribution patterns. Additionally, multi-source data were used to assess heat wave risk in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 66 publications
3
20
0
Order By: Relevance
“…By comparing the results with the 2015 global standard heat wave index distribution of Raei [50] and the Belt and Road regional HWR assessment of Yin [21], it is concluded that the regional HWR at the kilometer scale agrees well with that determined in previous large-scale studies in terms of the overall dynamics. The risk is higher in the northwestern part of the study area and the highest in the Jakarta region.…”
Section: Comparative Analysis Of the Heat Wave Risk Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…By comparing the results with the 2015 global standard heat wave index distribution of Raei [50] and the Belt and Road regional HWR assessment of Yin [21], it is concluded that the regional HWR at the kilometer scale agrees well with that determined in previous large-scale studies in terms of the overall dynamics. The risk is higher in the northwestern part of the study area and the highest in the Jakarta region.…”
Section: Comparative Analysis Of the Heat Wave Risk Resultssupporting
confidence: 72%
“…However, all of these indicators mentioned, including those considered relevant but not mentioned, need to be explored and will be considered for inclusion in future updates of this study once city-level or more detailed-level data are available. (3) Heat waves can be fatal in severe cases, so the number of heat-related deaths or the incidence of heat-related mortality best validates the HWR [5,21], but these data are currently difficult to obtain. The extraction of heat-related mortality data from all-cause mortality data and mortality data related to various diseases will be a key focus of future HWR studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, temperature change in China as a result of climate change has attracted a great deal of attention. Many studies revealed changes in temperature and extreme weather events over the past few decades [5][6][7][8]. Their choice of heat threshold has generally followed two approaches: (1) exceedance of fixed absolute values (e.g., 35 • C) or (2) deviation from normal.…”
Section: Introductionmentioning
confidence: 99%